2018
DOI: 10.1038/s41557-018-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

An artificial interphase enables reversible magnesium chemistry in carbonate electrolytes

Abstract: Magnesium-based batteries possess potential advantages over their lithium counterparts. However, reversible Mg chemistry requires a thermodynamically stable electrolyte at low potential, which is usually achieved with corrosive components and at the expense of stability against oxidation. In lithium-ion batteries the conflict between the cathodic and anodic stabilities of the electrolytes is resolved by forming an anode interphase that shields the electrolyte from being reduced. This strategy cannot be applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
318
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(321 citation statements)
references
References 47 publications
2
318
0
1
Order By: Relevance
“…Another surface modification method showed that by engineering a conductive layer on the Mg anode, a Mg cell can be constructed with a V 2 O 5 cathode and Mg[NTf 2 ] 2 electrolyte, even in the presence of H 2 O. This work has addressed the H 2 O passivating issue while maintaining the charge shielding effect of H 2 O with respect to Mg 2+ that is significant on the cathode . In other work, Chen et al.…”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another surface modification method showed that by engineering a conductive layer on the Mg anode, a Mg cell can be constructed with a V 2 O 5 cathode and Mg[NTf 2 ] 2 electrolyte, even in the presence of H 2 O. This work has addressed the H 2 O passivating issue while maintaining the charge shielding effect of H 2 O with respect to Mg 2+ that is significant on the cathode . In other work, Chen et al.…”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…Various modification methods to Mg anodes have been developed to diminish the influence of the passivation layer at the Mg electrode interface . It has been demonstrated that after surface treatment with Ti[NTf 2 ] 2 Cl 2 , the Mg anode was compatible with Mg[TFSI] 2 /DME/G2 based electrolytes.…”
Section: Rechargeable Mg Batteriesmentioning
confidence: 99%
“…When this electrolyte was used in the Mg/V 2 O 5 electrode system, a very low discharge capacity was achieved as a result of the high interfacial resistance at the Mg anode . One approach to achieve the efficient use of carbonate solvents was developed by Son et al., who engineered an artificial Mg 2+ ‐conductive interphase that consisted of the thermally cyclized polyacrylonitrile and Mg triflate (Mg(CF 3 SO 3 ) 2 ) on the Mg anode surface. The as‐prepared electronic‐insulating interphase with a thickness of about 100 nm can prevent the electrochemical reduction of the electrolytes, shows good compatibility with water, and allows Mg 2+ transfer (ionic conductivity: 1.19×10 −6 S cm −1 ).…”
Section: Halogen‐containing Electrolytes For Magnesium Batteriesmentioning
confidence: 99%
“…[47] As an analoguet ot he lithium-sulfur battery,m agnesiumsulfur battery was also proposed to achieveahigher full-cell energy density.T he magnesium-sulfur system can theoretically achieve ac apacity of 957 mA h À1 g À1 with ac ell voltage of 1.77 V. One of the most seriousp roblemst hat remainf or the magnesium-sulfur system is the electrolyte. [52] In their report, the overpotential of bare magnesium metal rapidly increased in 0.5 m MgTFSI/acrylonitrile (AN) electrolyte, whereas coated magnesium remained stable for over 1000 cycles. Muldoone tal.…”
Section: Magnesiummentioning
confidence: 99%